DELIVERY OF GOOD IN THE LOAN AGREEMENT: CONDITION OF VALIDITY OR OBLIGATION OF THE LENDER? - LIVIU STANCIULESCU (Challenges of the Knowledge Society, 2011)
In theory, the loan is generally defined as a contract whereby a person, called the lender, shall use or immovable property of another person, called the loan, which is obliged to repay in kind. Based on the definition above national doctrine is unanimous in determining that the loan is a unilateral contract, because creates obligations only for the borrower. Similarly, the loan is a real contract because the manifestation of will must be accompanied by delivery of the good. Given the above, the question is obvious: delivery of the borrowed good is a condition of validity of the contract (specific for its formation) or an obligation of the borrower (operating in the execution phase) ? Please note that determining the legal nature of the good delivery has great importance to the doctrine and practice. Thus, relative to the approach adopted: „delivery - a condition of validity” or „ delivery - obligation of the lender”, legal consequences are totally different, with direct implications in defining the actual contract, the contract unilaterally rescinded the conditions in which they operate, etc.. In our approach we try to demonstrate that good delivery in the loan agreement can only be an obligation of the borrower (with all consequences arising from such qualification).